Effects of void and temperature on fracture of Cu/Cu3Sn bilayers: A molecular dynamics study. (June 2022) - Wu, Cheng-Da; Liu, Kai-Wei
Abstract: The effects of a void and temperature on the fracture of Cu/Cu3 Sn bilayers (as solder joints in electronic packages) under a tensile test are studied using molecular dynamics simulations. The simulation results show that the failure of the bilayers without a pre-existing void is caused by the collapse of the layer interface, whereas that of those with a pre-existing void is dominated by a competition between the collapse of the layer interface and the growth of the pre-existing void. The Young's modulus of the bilayers significantly decreases with increasing temperature. The ultimate stress of the bilayers decreases with increasing temperature and initial void radius, and increases with increasing distance ( L ) between the void center inside Cu3 Sn and the interface. At room temperature, the bilayers have lower Young's modulus and ultimate stress and higher ultimate strain when their void (radius: ≤ 2 nm) is located at the interface compared to those of bilayers with a void far away from the interface (e.g., L = 2–4 nm). The tensile test at higher temperatures more significantly weakens the interfacial bonding of the Cu/Cu3 Sn bilayer, resulting in a quicker interface collapse. Graphical Abstract: ga1